Oenothein B Suppresses Lipopolysaccharide (LPS)-Induced Inflammation in the Mouse Brain - Okuyama, Satoshi (Molecular Diversity Preservation International (MDPI), 2013)
Oenothein B has been recently evaluated for its ability to affect inflammatory responses in peripheral tissues. In this study, we examined its effect on the damage to the central nervous system due to systemic inflammation. For this purpose, ICR mice were injected with an intraperitoneal (i.p.) dose of lipopolysaccharide (LPS; 1 mg/kg mouse). When oenothein B was administered per os (p.o.), it suppressed (1) LPS-induced abnormal behavior in open field; (2) LPS-induced microglial activation in the hippocampus and striatum; and (3) LPS-induced cyclooxygenase (COX)-2 production in the hippocampus and striatum of these mice. These results suggest that oenothein B had the ability to reduce neuroinflammation in the brain during systemic inflammation.